Opportunities for Physical Activity in the School Environment and Their Association with Physical Activity and Sedentary Behavior in Brazilian Adolescents - De Moraes-Ferrari, G (Nature Research, 2025)
The school environment (SE) plays a crucial role in determining adolescents’ physical activity (PA), including physical education classes, sports spaces and facilities, and active recreation. This study aimed to evaluate the association between the SE and indicators of PA and sitting time (ST), while exploring Brazilian sociodemographic differences. The SE was characterized by PA practices, PA outside regular class hours, running/athletic track condition, use of the courtyard for PA with a professional, participation in inter-school games or physical-sports competitions, and the number of physical education classes per week. PA and ST were assessed via self-report questionnaires, categorizing participants as active or insufficiently active for PA and as having low or excessive ST. The study included a nationally representative sample of 155,019 Brazilian adolescents (50.9% female). Among them, 28.5% were classified as active and 47.3% had adequate ST. Taking two or more physical education classes was positively associated with being active (OR: 1.669; 95% CI: 1.665–1.673) and with having low ST (OR: 1.050; 95% CI: 1.048–1.052). The association between SE characteristics and PA varied by region and school type (rural/urban, public/private), emphasizing that SE impacts PA and ST differently depending on the sociodemographic context of the adolescents. © The Author(s) 2025.